Fathers And Breastfeeding Process: Determining Their Role And Attitudes - Manar W Abu-Abbas; Manal I Kassab; Khitam I Shelash (European Scientific Journal, ESJ, 2016)
Breastfeeding is a vital for infants during their early stage of life and it is considered that fathers have an important role to make this process succeed; this study was done to determine father’s attitudes and involvement in the breastfeeding process. A study survey instrument designed to measure father’s attitudes regarding breastfeeding process, the degree of their involvement and fathers` surrounded cultural effect on their involvement. Instrument were piloted with 22 fathers who met the inclusion criteria and Cronbach's alpha was 0.73 for both measures : fathers` attitudes regarding breastfeeding and fathers` involvement in the process. Then a total of 198 fathers in King Abdullah University Hospital (KAUH) in Jordan completed a self-administered questionnaire. Means and standard deviations were calculated for the measures of fathers` breastfeeding attitudes and involvement, then Pearson’s correlation analysis was conducted with an alpha level of 0.05 between the measure of fathers` involvement in breastfeeding process and surrounded cultural effect on their involvement. Result shows that fathers in had a negative attitudes and poor involvement in the breastfeeding process, and a significant correlation found between fathers` involvement in the breastfeeding process and surrounded cultural effect regarding this role (P- value = 0.01). Father may play an important role to positively influence a mother's decision to initiate and continue breastfeeding. Therefore, efforts to increase breastfeeding rates should focus on involving fathers in interventions and programs to change their attitudes and make them aware regarding their role in the breastfeeding process.